India : The Regulation of Microfinance - An Analysis of Recent Proposals - World Bank (Washington, DC, 2013)
The Indian microfinance community has been pushing for legal and regulatory reform for several years, motivated primarily by two desires: (i) formal legal recognition and legitimization of the various types of microfinance institutions (MFIs) operating in India and (ii) legal permission to engage in deposit-taking with lower and fewer entry barriers. Members of the microfinance community have engaged with the Government of India in a dialogue regarding the regulation of microfinance service delivery, arguing that there is a need for reform to facilitate expansion of outreach through microfinance to the millions of Indians who currently do not have access to financial services. Various stakeholders have proposed a range of possible reform measures, which vary in their approaches and in their potential effects on the microfinance sector.